Association between cerebral amyloid accumulation and synaptic density in Alzheimer's disease: A multitracer PET study: Neuroimaging: Imaging the human synapse in AD. (7th December 2020) - O'Dell, Ryan S.; Mecca, Adam P.; Chen, Ming‐Kai; Godek, Tyler A.; Harris, Joanna E.; Bartlett, Hugh H.; Banks, Emmie R.; Kominek, Victoria L.; Zhao, Wenzhen; Naganawa, Mika; Toyonaga, Takuya; Lu, Yihuan; et al.
Abstract: Background: Synaptic loss is an early pathology in Alzheimer's disease (AD) and the major structural correlate of cognitive impairment. We have recently demonstrated extensive synaptic loss in medial temporal and neocortical brain regions of participants with AD. In this study, we further investigate the association of global and local amyloid burden with synaptic density in AD using [ 11 C]UCB‐J PET. Method: [ 11 C]UCB‐J and [ 11 C]PiB binding were measured in 38 participants with AD and 19 cognitively normal participants aged 55‐85 years. For [ 11 C]PiB analysis, parametric images of binding potential ( BPND ) were generated using SRTM2 with cerebellum as a reference region and converted to distribution volume ratios ( DVR ). For [ 11 C]UCB‐J, BPND was computed using SRTM2 with a shrunken centrum semiovale reference region and converted to DVR with a cerebellum reference region. Result: The AD group showed significant widespread reductions in cortical and subcortical synaptic density, most pronounced in medial temporal lobe, and significantly elevated cortical amyloid in regions commonly affected by AD pathology (Figure 1). Among pooled participants (n=57), higher global amyloid burden was associated with lower synaptic density in the majority of regions. Significant negative associations between local amyloid and SV2A were also observed across the majority of cortical regions in the pooled sample (lateral temporal, prefrontal, posterior cingulate/precuneus, lateral parietal, and lateral occipital; r=‐0.29 to ‐0.48, p<0.05) with the exception of medial temporal (r=‐0.18, p=0.17), anterior cingulate (r=‐0.19, p=0.15), and pericentral (r=‐0.23, p=0.08) cortices (Figure 2). These significant associations between either global or regional amyloid and SV2A were not observed in analyses restricted to the AD group, in both an region‐ or surface‐based analysis (Figure 3). Conclusion: Using [ 11 C]UCB‐J PET, widespread reductions of synaptic density were observed in AD participants. Cortical regions associated with the least accumulation of fibrillar amyloid (medial temporal lobe) were associated with the most pronounced reductions in synaptic density. Significant negative associations between both global and local amyloid and synaptic density in the pooled sample were driven by group differences, and not significant within the AD group alone. Our findings are consistent with postmortem studies describing the patterns of fibrillar amyloid burden and synaptic loss in AD.